Rapid and Low Cost Manufacturing of Cuff Electrodes - Flavin, Matthew T.; Paul, Marek A.; Lim, Alexander S.; Abdulhamed, Senan; Lissandrello, Charles A.; Ajemian, Robert; Lin, Samuel J.; Han, Jongyoon (Frontiers in Neuroscience, 2021)
For many peripheral neuro-modulation applications, the cuff electrode has become a preferred technology for delivering electrical current into targeted volumes of tissue. While basic cuffs with low spatial selectivity, having longitudinally arranged contacts, can be produced from relatively straightforward processes, the fabrication of more complex electrode configurations typically requires iterative design and clean-room fabrication with skilled technicians. Although facile methods for fabricating cuff electrodes exist, their inconsistent products have limited their adoption for rapid manufacturing. In this article, we report a fast, low-cost fabrication process for patterning of electrode contacts in an implantable peripheral nerve cuff. Using a laser cutter as we have prescribed, the designer can render precise contact geometries that are consistent between batches. This method is enabled by the use of silicone/carbon black (CB) composite electrodes, which integrate with the patterned surface of its substrate—tubular silicone insulation. The size and features of its products can be adapted to fit a wide range of nerve diameters and applications. In this study, we specifically documented the manufacturing and evaluation of circumpolar cuffs with radial arrays of three contacts for acute implantation on the rat sciatic nerve. As part of this method, we also detail protocols for verification—electrochemical characterization—and validation—electrophysiological evaluation—of implantable cuff electrodes. Applied to our circumpolar cuff electrode, we report favorable electrical characteristics. In addition, we report that it reproduces expected electrophysiological behaviors described in prior literature. No specialized equipment or fabrication experience was required in our production, and we encountered negligible costs relative to commercially available solutions. Since, as we demonstrate, this process generates consistent and precise electrode geometries, we propose that it has strong merits for use in rapid manufacturing.